5-HT2A and mGlu2/3 receptor interactions: on their relevance to cognitive function and psychosis. Issue 1 (February 2016) - Wischhof, Lena; Koch, Michael
Abstract : Serotonin [5-hydroxytryptamine (5-HT)] and glutamate have both been implicated in the pathophysiology of neuropsychiatric disorders but also in the mechanism of antipsychotic and hallucinogenic drug actions. Furthermore, close antagonistic interactions between 5-HT2A and metabotropic glutamate (mGlu)2/3 receptors have been established over the last decades on the basis of numerous electrophysiological, biochemical, and behavioral studies. Besides synaptic mechanisms, more recent findings suggested that heterodimeric 5-HT2A –mGlu2 receptor complexes in the prefrontal cortex may account for the functional crosstalk between these two receptor subtypes. In this review, we focus on in-vitro and in-vivo studies documenting the important relationship between 5-HT2A and mGlu2/3 receptors, with relevance to both normal behavioral function and psychosis.